STRENGTHENING THE SAFETY NET, PROTECTING WOMEN JUSTICE SEEKERS FROM THE CLUTCHES OF JUSTICE BROKERS - Nasrudin, Muhamad; Zulaikha, Siti; Lestari, Enny Puji (Universitas Islam Negeri Mataram, 2024)
Female justice seekers are vulnerable and find it difficult to access justice due to psychological factors (fear, inferiority, nervousness), financial problems, limited access to facilities and resources, limited knowledge in the legal field, and negative stigma about going to court. In these circumstances, East Lampung district may turn to the pamong desa (village officials). Unfortunately, village officials sometimes act as justice brokers, preventing women from further accessing justice. This paper refers to how the safety net was built and strengthened to protect justice seekers from the clutches of justice brokers. Therefore, this paper uses qualitative research with a socio-legal approach. Data was collected through conversation and focused group discussion among village officials, religious counselors, the Office of Religious Affairs (KUA), and Rumah Perempuan dan Anak (RPA) Lampung Timur to strengthen the position of female justice seekers. The data was analyzed using feminist legal studies, access to justice, and mediation as a framework. As a finding, female justice seekers are vulnerable and have limited access. Therefore, support should be provided by close community assets, namely religious counselors and village officials. These two parties need to be strengthened in terms of understanding the importance of the perspective of vulnerable women as legal subjects, prioritizing the interests of victims, the urgency of resolving both litigious and non-litigious cases, strengthening close, trusted networks, consolidating and distributing roles among community assets, strengthening mediation and advocacy skills, strengthening the role of the KUA and its assets, strengthening preventative functions, and strengthening the economic family based on the uniqueness of the village.